ASSISTING MSMES IN KLAKEH VILLAGE, BANGILAN DISTRICT, IN MARKETING PRODUCTS THROUGH ONLINE AND OFFLINE MEDIA - Anisah, Zilfatun; Irawan, Agus Wahyu; Suyanto, Ahmad (Journal of Community Engagement in Economics, 2024)
The assistance provided to Micro, Small, and Medium Enterprises (MSMEs) in Klakeh Village, Bangilan District, focuses on enhancing product marketing capabilities through online and offline media. This study aims to address the challenges faced by MSMEs, such as limited knowledge of technology and marketing strategies. The Community Based Research (CBR) method was used in this study, involving active collaboration between researchers and the local community. The results of the study showed a significant increase in MSMEs' marketing knowledge and skills after receiving assistance. Through a series of training sessions, MSME actors were able to understand online marketing techniques, such as the use of social media, creative content creation, and search engine optimization (SEO). Additionally, they learned offline marketing strategies, such as branding, product packaging, and direct sales techniques. The implementation of these marketing strategies helped MSMEs in Klakeh Village expand their market reach to the national level, as well as increase sales and product image. This assistance also empowered the community by enhancing their sense of ownership and responsibility for the sustainability of the program. The program evaluation revealed the need to expand partnerships with e-commerce platforms and improve access to technology to boost the competitiveness of MSMEs. With the implementation of these recommendations, it is hoped that MSMEs in Klakeh Village can continue to develop and compete in a broader and more competitive market, supporting sustainable local economic growth.